Analisis Quality of Service (QOS) Jaringan Internet Fakultas Teknik Universitas Muhammadiyah Makassar - Akbar Akbar; Saiful Saiful (Ainet : Jurnal Informatika, 2019)
Analysis Quality of Service (QoS) Internet Network Faculty of Engineering, University of Muhammadiyah Makassar guided by Zahir Zainuddin and Rahmania. QoS parameters were observed or measured is Bandwidth, Delay, Packet Loss and throughput. This research was conducted at the Faculty of Engineering, University of Muhammadiyah Makassar, this study aims to measure, analyze and determine Kualitias Internet Network Engineering Faculty of Muhammadiyah University Makassar. To measure Delay, Packet lost and throughput using software Axence NetTools 4.0 Pro. The results of measurements of parameters of Quality of Service (QoS) Internet network is measured is the bandwidth available on Thursday, Friday and Saturday = 10240 Kbps. Delay highest in the can on Thursday = 74.66 ms, while the lowest in the delay may be on Saturdays = 62 ms. Packet loss is the highest obtained on Thursday = 5.33%, while the lowest in the lost packet can be on Saturdays = 0.33%. The highest throughput in the can on Saturdays = 357 106 bps, while the lowest in the throughput can be on Thursday = 278 039 Bps. Based on the data delay and packet loss above, Internet Network Quality Faculty of Engineering, University of Muhammadiyah Makassar categorized as very good.